Crumble and meal ration evaluate to Nile tilapia (Oreochromis niloticus) larvae during sexual reversion phase - DOI: 10.4025/actascianimsci.v26i2.1865 - Bombardelli, Robie Allan (2008)
The objective from this work was evaluate the effect of ration processing to Oreochromis niloticus L. larvae, on survival, performance and sexual reversal efficiency in sex revert phase. The experimental period were 30 days, and it was utilized a completely randomized design with tree treatments and six replications. An experimental unit was consist of 12L aquarium, with 20 larvae. The first treatment was consist of only meal ration utilization; the second treatment utilized a meal ration until 10th day and after crumble ration; and the third treatment utilized meal ration until 20th day and after crumble ration. At the end of the experiment, there were analysed weight, lenght, mortality and sex reversal. The data were submitted to analysis of variance and didn’t present differences (P>0.05) among treatments. The meal ration can be utilized without damage on performance, survival, or sexual reversal efficiency, to Nile tilapia during sex reversion phase.